Hikmah wahyu Ilahy: sebab-sebab turunnya ayat suci al qur'an disertai penjelasan - Bachtiar Affandi (Jasana, 1975)
ir, jil.1,c.1 ; jil.2,c.1/oen, jil.3=c.1/oen, jil.1=c.2 ; jil.1,c.3/stc13,jil.2,c.1 ; jil.1,c.3